PERANCANGAN PMSG UNTUK PEMBANGKIT LISTRIK SKALA MIKRO DENGAN NILAI COGGING TORQUE RENDAH - Ujang Cakra Buana; Dian Budhi Santoso (BAROMETER, 2022)
The need for electrical energy continues to increase along with population growth. it is very important to encourage the use of new and renewable energy to support electricity needs. One of them is the use of wind energy. Wind can be used to drive a turbine coupled to a generator. Permanent magnet synchronous generator (PMSG) is a type of generator that is often used in the utilization of wind energy. The main component of PMSG consists of three components, namely the stator, rotor and permanent magnet. The interaction between the components causes a ripple or often referred to as the cogging phenomenon. Cogging is what makes PMSG not work perfectly. This study discusses the effect of teeth width on decreasing the cogging torque value in PMSG by making two designs. The design variations used are teeth width 7 mm and 4 mm, Carpenter type of iron core: Silicon steel, Permanent magnet synchronous generator 18 slot 16 pole (PMSG 18s16p). The result of decreasing the value of cogging torque obtained is 0.012676 Nm with 4 mm teeth width. For numerical analysis using the finite element method (FEM).